Pembuatan lilin aroma terapi menggunakan sarang lebah dan ekstrak lemon di Kelurahan Sungai Pagar Kecamatan Kampar Kiri Kabupaten Kampar - Silvia Reni Yenti; Ahmad Fadli; Zultiniar Zultiniar; Sunarno Sunarno (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Village development is one of the national development interests in which universities contribute to the implementation of the Community Work Program (KUKERTA) in the form of Community Service in a designated area. Kampar is one of the areas that has the biggest honey sialang potential in Riau Province, one of which is Sungai Pagar sub-district, Kampar Kiri Hilir sub-district. Honey honeycomb processing that is not processed optimally can provide the latest innovation, namely the making of aromatherapy candles by using honeycomb and lemon extract. This dedication activity aims to provide new knowledge expertise to the community of Sungai Pagar sub-district as one form of efforts in increasing national development. A series of activities include counseling or outreach, training in aromatherapy candle making, packaging and marketing. This activity gave a positive response from the Sungai Pagar community by forming a collaboration between the KUKERTA Community Service Team and Imbo Kaluang UKM. The outputs generated from these community service activities are aromatherapy candle products, Appropriate Technology Book (TPG), mass media publications (print and online) and journal publications.